Real-world effectiveness of GLP-1 receptor agonist-based treatment strategies on “time in range” in patients with type 2 diabetes - Chen, Yongru; Chen, Jingxian; Zhang, Shuo; Zhu, Dan; Deng, Feiying; Zuo, Rui; Hu, Yufei; Zhao, Yue; Duan, Yale; Lin, Benwei; Chen, Fengwu; Liang, Yun; et al. (Frontiers in Pharmacology, 2024)
Background: Diabetes affects millions of people worldwide annually, and several methods, including medications, are used for its management; glucagon-like peptide-1 receptor agonists (GLP-1RAs) are one such class of medications. The efficacy and safety of GLP-1Ras in treating type 2 diabetes mellitus (T2DM) have been assessed, and have been shown to significantly improve Time in Range (TIR) in several clinical trials. However, presently, there is a lack of real-world evidence on the efficacy of GLP-1RAs in improving TIR. To address this, we investigated the effect of GLP-1RAbased treatment strategies on TIR among patients with T2DM in real-world clinical practice. Methods: This multicenter, retrospective, real-world study included patients with T2DM who had previously used a continuous glucose monitoring (CGM) system and received treatment with GLP-1RAs or oral antidiabetic drugs (OADs). Patients who received OAD served as controls and were matched in a 1:1 ratio to their GLP-1RA counterparts by using propensity score matching. The primary endpoint was the TIR after 3-6 months of treatment.Results: According to propensity score matching, 202 patients were equally divided between the GLP-1RA and OAD groups. After 3-6 months of treatment, the TIR for the GLP-1RA and OAD groups was 76.0% and 65.7%, respectively (p < 0.001). The GLP-1RA group displayed significantly lower time above range (TAR) and mean glucose values than the OAD group (p < 0.001). Subgroup analysis revealed that, compared with the administration of liraglutide, the administration of semaglutide and polyethylene glycol loxenatide (PEG-Loxe) significantly improved TIR over 3-6 months of treatment (p < 0.05).Conclusion: These real-world findings indicate that GLP-1RA-based treatment strategies could be superior to oral treatment strategies for improving TIR among patients with T2DM and that onceweekly GLP-1RA may be more effective than a once-daily GLP-1RA.Clinical trial registration: Chinese Clinical Trial Registry (http://www.chinadrugtrials.org.cn/index.html); identifier number: ChiCTR2300073697.